2005
DOI: 10.1038/nsmb904
|View full text |Cite
|
Sign up to set email alerts
|

Actin and hnRNP U cooperate for productive transcription by RNA polymerase II

Abstract: To determine the role of actin-ribonucleoprotein complexes in transcription, we set out to identify novel actin-binding proteins associated with RNA polymerase II (Pol II). Using affinity chromatography on fractionated HeLa cells, we found that hnRNP U binds actin through a short amino acid sequence in its C-terminal domain. Post-transcriptional gene silencing of hnRNP U and nuclear microinjections of a short peptide encompassing the hnRNP U actin-binding sequence inhibited BrUTP incorporation in vivo. In livi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
213
2
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(227 citation statements)
references
References 45 publications
11
213
2
1
Order By: Relevance
“…hnRNPU-B23 interaction is mediated by histone-binding domain of B23 and RNA-binding domain of hnRNPU Both B23 and hnRNPU were known to contain functional domains, which account for their distinctive biochemical functions (Hingorani et al, 2000;Kukalev Figure 1 B23 interacts with hnRNPA1 and hnRNPU in the cytosol on ActD treatment. (a) HeLa cells stably expressing GFP were treated with the 0.1% DMSO vehicle, CHX (25 mg/ml) and ActD (1 mg/ml), respectively, followed by immunostaining with anti-B23 antibody (red).…”
Section: B23 Binds To Hnrnpu and Hnrnpa1 In The Cytosol In Response Tmentioning
confidence: 99%
See 1 more Smart Citation
“…hnRNPU-B23 interaction is mediated by histone-binding domain of B23 and RNA-binding domain of hnRNPU Both B23 and hnRNPU were known to contain functional domains, which account for their distinctive biochemical functions (Hingorani et al, 2000;Kukalev Figure 1 B23 interacts with hnRNPA1 and hnRNPU in the cytosol on ActD treatment. (a) HeLa cells stably expressing GFP were treated with the 0.1% DMSO vehicle, CHX (25 mg/ml) and ActD (1 mg/ml), respectively, followed by immunostaining with anti-B23 antibody (red).…”
Section: B23 Binds To Hnrnpu and Hnrnpa1 In The Cytosol In Response Tmentioning
confidence: 99%
“…Protein hnRNPU, another hnRNPs family member, is able to stabilize specific mRNAs by binding to their 3 0 -untranslated regions (UTRs) (Yugami et al, 2007). Moreover, hnRNPU has a regulatory function during the initial phases of transcription activation by affecting the activity of RNA Pol II (Kukalev et al, 2005).…”
mentioning
confidence: 99%
“…Nuclear ␤-actin associates with components of the ATP-dependent chromatin-remodeling complexes (Olave et al, 2002;Bettinger et al, 2004), with RNP particles (Percipalle and Visa, 2006), and with the three RNA polymerases in the eukaryotic cell nucleus, both in vitro and in vivo (Hu et al, 2004;Philimonenko et al, 2004;Kukalev et al, 2005;Wu et al, 2006). The above studies have shown that nuclear actin is a component of large protein complexes that include RNA polymerases, transcription elongation factors, and accessory splicing factors that can be recruited to the RNAPII carboxy terminal domain and hence to promoters.…”
Section: Introductionmentioning
confidence: 99%
“…The endogenous proteins physically interact via the zinc-fingers of WT1 and the middle domain of hnRNP-U, the interaction is direct and hnRNP-U can inhibit WT1-mediated transcriptional activation. hnRNP-U has been shown to regulate splicing and RNA transport as well as transcription (Kanai et al, 2004;Kukalev et al, 2005). Similar roles have been proposed for WT1 (Davies et al, 1998;Ladomery et al, 1999;Niksic et al, 2004), so the interaction with hnRNP-U could potentially regulate any of these processes.…”
Section: Antibody (C Es Cells; D M15 Cells) (E)mentioning
confidence: 87%
“…This transcriptional inhibition by hnRNP-U was shown to involve the middle domain of hnRNP-U, the same domain that associates with WT1, suggesting that the hnRNP-U:WT1 interaction may mediate transcriptional inhibition by bringing hnRNP-U into the proximity of RNA polymerase II via WT1-binding sites in the promoters of target genes. In addition, a search for novel actin-binding proteins associated with RNA polymerase II identified hnRNP-U (Kukalev et al, 2005) and showed that both actin and hnRNP-U associate with the phosphorylated form of RNA polymerase II and are implicated in the initial phases of transcription. In the present study, we also detected a protein that matched either g-or b-actin in the MS-FIT database as immunoprecipitating with WT1 (Table 2.1).…”
mentioning
confidence: 99%